Factors Influencing the Semantic Context Benefit to Foreign-accented Word Recognition - Kailun Zhao (Journal of Linguistics and Communication Studies, 2024)
The current review discusses about the nature of semantic context benefit in accented listening comprehension by reviewing and analyzing the main listener and stimulus factors influencing the benefit of semantic context. This review investigates the impact of various factors, including age, vocabulary knowledge, second language proficiency, accent strength, noise interference, and accent familiarity, on the effectiveness of semantic context in aiding the comprehension of accented speech. Semantic context plays a crucial role in facilitating comprehension but its efficacy varies across different characteristics. Understanding these factors can inform the development of effective strategies for improving accented speech perception and optimizing language learning environments. Identifying the interplay between these variables is essential for addressing challenges in intercultural communication and promoting linguistic diversity in multilingual contexts.